Factors that influence the scale up of new interventions in low-income settings: a qualitative case study of the introduction of chlorhexidine cleansing of the umbilical cord in Bangladesh. Issue 4 (18th February 2020) - Callaghan-Koru, Jennifer A; Islam, Munia; Khan, Marufa; Sowe, Ardy; Islam, Jahrul; Mannan, Imteaz Ibne; George, Joby; ,
Abstract: There is a well-recognized need for empirical study of processes and factors that influence scale up of evidence-based interventions in low-income countries to address the 'know-do' gap. We undertook a qualitative case study of the scale up of chlorhexidine cleansing of the umbilical cord (CHX) in Bangladesh to identify and compare facilitators and barriers for the institutionalization and expansion stages of scale up. Data collection and analysis for this case study were informed by the Consolidated Framework for Implementation Research (CFIR) and the WHO/ExpandNet model of scale up. At the national level, we interviewed 20 stakeholders involved in CHX policy or implementation. At the district level, we conducted interviews with 31 facility-based healthcare providers in five districts and focus group discussions (FGDs) with eight community-based providers and eight programme managers. At the community level, we conducted 7 FGDs with 53 mothers who had a baby within the past year. Expanded interview notes were thematically coded and analysed following an adapted Framework approach. National stakeholders identified external policy and incentives, and the engagement of stakeholders in policy development through the National Technical Working Committee for Newborn Health, as key facilitators for policy and health systems changes. Stakeholders, providers and families perceived the intervention to be simple, safe and effective, and more consistent with family preferences than the prior policy of dry cord care. The major barriers that delayed or decreased the public health impact of the scale up of CHX in Bangladesh's public health system related to commodity production, procurement and distribution. Bangladesh's experience scaling up CHX suggests that scale up should involve early needs assessments and planning for institutionalizing new drugs and commodities into the supply chain. While the five CFIR domains were useful for categorizing barriers and facilitators, additional constructs are needed for common health systems barriers in low-income settings.